The Correlations Between Economic Growth and Socio-Economic Indicators in Nagan Raya Regency - Noviyanti, Mariska; Noviar, Helmi; Badli, Saiful (Gorontalo State University, 2024)
This study aims to examine the relationship between economic growth and poverty, income inequality, and the quality of human resources. This study uses secondary data, namely time series data over 15 years from 2007-2021. The results of the empirical research show that economic growth is weakly correlated with poverty, income inequality, and human resource quality. In addition, it does not show any causal relationship. However, it is interesting that there is a negative correlation between poverty and the human development index and a positive and negative correlation between poverty and inequality. Several policy implications are recommended to the government about the results of the study and empirical analysis.